351 Prevalence and prognostic significance of RV uptake (biventricular uptake) at planar scintigraphy in patients with ATTR cardiac amyloidosis. (8th December 2021) - Porcari, Aldostefano; Pagura, Linda; Canepa, Marco; Biagini, Elena; Cappelli, Francesco; Gagliardi, Christian; Longhi, Simone; Tini, Giacomo; Dore, Franca; Bonfiglioli, Rachele; Bauckneht, Matteo; Miceli, Alberto; et al.
Abstract: Aims: The validation of cardiac scintigraphy with bone tracers for nonbiopsy confirmation of transthyretin cardiac amyloidosis (ATTR-CA) has revolutionized the diagnosis of this condition. While most studies focused on left ventricle (LV) uptake, the significance of bone tracers uptake in the right ventricle (RV) leading to biventricular (BiV) uptake has not been investigated so far. BiV uptake at planar scintigraphy might reflect a more advanced ATTR-CA. To estimate the prevalence of BiV uptake and its potential prognostic role in ATTR-CA. Methods and results: Multicentre, retrospective, observational study performed among four Italian referral centres for CA. Data of ATTR-CA patients who underwent bone tracers scintigraphy with acquisition of planar and SPECT imaging between November 2014 and June 2020 at participating centres were centrally revised. ATTR-CA was diagnosed according to the Gilmore's algorithm. LV uptake was assessed by Perugini visual scale. RV uptake was defined as: 0 = absent, 1 ≤ bone uptake, 2 = equal to bone uptake, and 3 ≥ bone uptake. Images were independently assessed by six experienced operators, blinded to all patients' data. Cardiological data included clinical examination, ECG, echocardiography and blood tests. The primary outcome was a composite of cardiac death and hospitalization for heart failure. Of the 124 patients with ATTR-CA included in this analysis, 93 (75%) had BiV uptake at planar scintigraphy and all had RV free wall uptake confirmed at SPECT imaging. The prevalence of planar BiV uptake increased along with the LV Perugini grade: 14% in Perugini grade 1, 70% in Perugini grade 2, and 92% in Perugini grade 3. Compared to those with planar LV uptake, patients with planar BiV uptake were older (81 vs. 77 years, P = 0.006), more frequently in NYHA ≥3 (32% vs. 10%, P = 0.018), had increased NT-proBNP values (4293 vs. 2492 pg/ml, P = 0.046), LV wall thickness (18 vs. 17 mm, P = 0.007). They had higher rates of LV ejection fraction <50% (42% vs. 10%, P = 0.001) and lower TAPSE (16 vs. 20 mm, P = 0.048). At 18 months, patients with BiV uptake experienced the primary endpoint more frequently than those with LV uptake ( P = 0.021, Figure), with the highest risk observed in patients with grade 2–3 RV uptake ( P = 0.010). The LV Perugini grade did not affect prognosis ( P = 0.20). At multivariate analysis, NYHA ≥3, eGFR <60 ml/min and BiV uptake had independent prognostic value (HR 8.0, P = 0.007; HR 2.1, P = 0.025; HR 1.7, P = 0.007; respectively). Conclusions: The presence of BiV uptake at planar scintigraphy identified ATTR-CA patients at worse cardiovascular outcome, potentially serving as novel marker for prognostic stratification in this population.